Hirarki Maqāṣid Syarī‘ah dalam Penentuan Usia Minimal Perkawinan: Analisis Normatif atas Dharuriyyāt, Hājiyyāt, dan Taḥsīniyyāt (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The determination of a minimum marriage age is a central issue in Indonesian family law and Islamic legal discourse, particularly regarding the prevention of health, social, and psychological risks associated with child marriage. This study analyzes the alignment between the legal requirement of a minimum age of 19, as stipulated in Law No. 16 of 2019 and Constitutional Court Decision No. 22/PUU-XV/2017, and the framework of maqāṣid sharī‘ah, especially the hierarchical structure of dharuriyyāt, ḥājiyyāt, and taḥsīniyyāt. Employing a normative juridical method supported by extensive literature review, this research examines statutory regulations, classical and contemporary Islamic legal sources, works on maqāṣid, and empirical data from national and international institutions. The findings demonstrate that the minimum age of 19 substantively accords with maqāṣid sharī‘ah: at the dharuriyyāt level, it safeguards life, intellect, and lineage from medical, psychological, and social harm; at the ḥājiyyāt level, it prevents economic hardship, emotional instability, and the inability of young couples to assume household roles; and at the taḥsīniyyāt level, it preserves human dignity, ethical conduct, and the sanctity of marriage. Consequently, the regulation is not a departure from classical Islamic jurisprudence but rather an implementation of public interest (maṣlaḥah) adapted to contemporary societal realities. This study affirms that integrating maqasid-based reasoning into public policy strengthens the protection of families and future generations in Indonesia.